Experimental investigation and optimization of machining parameters of deep cryogenically treated and tempered steels in electrical discharge machining process. (October 2022) - Kam, Menderes; İpekçi, Ahmet; Argun, Kudbeddin
Electrical Discharge Machining (EDM) is commonly used as non-traditional manufacturing methods for geometrically complex shaped or hardened materials that are extremely difficult-to-machine with traditional machining processes. In this experimental study, investigations were carried out on the machining of Conventional Heat Treated three different deep cryogenically treated and tempering processes (DCT&T) of AISI 4140 steels in EDM process. The process parameter such as discharge current (9, 16, 23, and 30 A), pulse on time (120, 180, 240, 300 µs) and pulse off time (12, 18, 24, and 30 µs) were investigated and the output responses like surface roughness, electrode wear ratio, material removal rate, and machining time were explored. Experiments were conducted using L16 orthogonal array in EDM machining process. The data obtained from experiments were analyzed. As a result, determination of discharge current (30 Amps), pulse off time (12 to 18 µs), pulse on time (180 to 240 µs) and deep cryogenically treatment with 24 h and 48 h holding time as the optimum machining processing parameters for tempered steels to be subjected to DCT&T process. As a result of multi-criteria optimization, it is suitable for best surface quality and fast material removal rate.